A study on the accessibility and utilisation of targeted drugs for pulmonary arterial hypertension in China - Li, Wei; Zhang, Han; Xu, Lulu; Tang, Wan; Lu, Wei; You, Zhengyi; Wu, Huanhuan; Lin, Yanquan; Chen, Hongdou (Frontiers in Pharmacology, 2026)
ObjectiveThis study aimed to evaluate the availability, price levels, affordability, and utilisation of targeted drugs for pulmonary arterial hypertension (PAH) in China.MethodsThis study utilized a retrospective longitudinal design, based on drug procurement data from 859 public hospitals in China, covering the period from January 2019 to December 2023. Accessibility of 11 PAH-targeted therapies was evaluated across three key dimensions: availability (proportion of hospitals stocking the drug), price level (the Defined Daily Dose cost, namely, DDDc = Total annual drug expenditure/DDDs of the drug), and affordability (out-of-pocket expenses as a percentage of household disposable income).ResultsWhile there was a significant overall improvement in the accessibility of PAH-targeted drugs, structural disparities in accessibility were evident across different drug types, hospital tiers, and between urban and rural areas, as well as among income groups. Availability data showed that tertiary hospitals had significantly better access to NMI-negotiated drugs than secondary hospitals (p = 0.006). Among all drugs, treprostinil had the highest availability (56.1% across hospitals), while newer drugs such as selexipag had very low availability (<10%). Price analysis revealed that the DDDc for most drugs had significantly decreased, including sildenafil (−91.0%) and macitentan (−95.2%), while iloprost remained costly (>3,700 CNY). In terms of affordability, in 2023, all drugs were affordable for the highest-income urban groups, while no drugs were affordable for the lowest-income rural groups, with the cost burden of iloprost accounting for 8,454.8% of the disposable income of the rural population. Drug accessibility exhibited significant structural imbalances, with some drugs being “affordable but hard to obtain” (e.g., riociguat) and others “highly burdensome and poorly accessible” (e.g., treprostinil).ConclusionThe findings demonstrate significant improvements in the affordability and availability of PAH-targeted therapies over the study period; however, notable inequalities persist in accessibility improvements across urban and rural areas and income groups. Future policies should be tailored to address specific accessibility challenges for different drug categories and focus on overcoming medication access barriers for low-income rural populations to foster health equity.